Combined effects of melatonin and topical hypothermia on renal ischemia-reperfusion injury in rats - Souza,Pablo Cambeses (2018)
Abstract Purpose: To evaluate whether their combination was more effective than either alone in decreasing renal damage due to ischemia/reperfusion (I/R) injury in rats. Methods: Thirty-two Wistar rats were assigned to four groups. Following right nephrectomy, their left kidneys were subjected to warm ischemia (IR), cold ischemia (TH+IR), intraperitoneal injection of 10 mg/kg melatonin (MEL+IR), or injection of 10 mg/kg melatonin followed by cold ischemia (MEL+TH+IR). Eight randomly assigned right kidneys constituted the control group. After 240 min of reperfusion, left nephrectomy was performed for histopathological evaluation, lipid peroxidation, and measurement of antioxidant enzyme activity. Serum was collected to measure urea and creatinine concentrations. Results: Histopathological damage induced by ischemia and reperfusion was more attenuated in the MEL+TH+IR group than in the MEL+IR and TH+IR groups (p<0.037). Superoxide dismutase activity was significantly higher (p<0.029) and creatinine (p<0.001) and urea (p<0.001) concentrations were significantly lower in the MEL+TH+IR group than in the MEL+IR and TH+IR groups. Conclusion: The combination of melatonin (MEL) and topical hypothermia (TH) better protects against renal I/R injury than does MEL or TH alone.